Rice husk valorization into sustainable Ni@TiO2/biochar nanocomposite for highly selective Pb (II) ions removal from an aqueous media. (May 2023) - Kamran, Urooj; Lee, Seul-Yi; Rhee, Kyong Yop; Park, Soo-Jin
Abstract: Herein, we successfully prepared sustainable nanocomposites from agriculture waste (rice husk)-derived biochar precursor, and followed by nickel-doped, base-treated titanium dioxide nanomaterials loading for efficient lead (Pb 2+ ) removal from aqueous media. By varying the loading contents of active materials, the optimized sample (Ni 0.01 @Na–TiO2 /BC) possessed an efficient Pb 2+ adsorption capability of 122.3 mg g −1 under the under optimum adsorption parameters, which is attributable to its specific surface area (138.09 m 2  g −1 ) and excess functional sites. Kinetic and Isothermal examination illustrated that Pb 2+ adsorption phenomena was well followed through pseudo 2nd order and Langmuir models. In addition, superior Pb 2+ ions adsorption selectivity was recorded by optimized sample in a multi-metallic system over other existing ion (such as Cd 2+, Mg 2+, Ca 2+, Cu 2+, and Zn 2+ ). Desorption experiments has been performed by using desorbing agent that demonstrates the good regeneration ability of sample. Hence, these findings provide new insight for the biowaste management by converting them into innovative adsorbents for commercial scale environmental remediation. Graphical abstract: Image 1 Highlights: Sustainable Ni x @Na–TiO2 /BC samples prepared for highly selective Pb 2+ removal. Ni@TiO2 loading impact towards improved properties and performance was evaluated. Maximum recorded Pb 2+ adsorption capacity under optimum condition was 122.3 mg g −1 . Ni x @Na–TiO2 /BC exhibited efficient Pb 2+ adsorption selectivity and recyclability.